Saberes, aprendizagens e estratégias articuladas por mulheres na busca por parir com dignidade no Ceará - Sales, Carolina Bentes de Oliveira (2024)
This dissertation narrates childbirth stories of women from Itapipoca, a town in the countryside of Ceará, in order to investigate their learning process about labour, birth and the development of strategies aimed at seeking safe care to prevent obstetric violence. For this purpose, we analyzed how the narratives of these women describe the childbirth care scenario and reflect on their own experiences. With this goal in mind, a qualitative research project was developed with characteristics that converge towards ethnography. Over a period of 3 years, intermittently and influenced by the COVID-19 pandemic, a field research was conducted using a snowball sampling method, in which pregnant, postpartum and elderly women, along with midwives from three different locations (urban center, indigenous community, quilombola community) were interviewed. From these interviews, we observed that there were predominantly negative reports regarding childbirth care at the main maternity hospital in the city center. These narratives also showed that during prenatal care at health clinics, there is a lack of discussion that helps women understand the risks and benefits of each childbirth method. Similarly, we do not find, most of the time, dialogue about sexuality and childbirth within families. Thus, we analyze how these women create their own strategies in the pursuit of dignified childbirth. The "choice" for cesarean surgery is among the main responses to avoid pain and a violent labour and birth assistance. However, this would be an illusion of freedom, since there is not enough information available to make a proper decision. After all, we live in a country that ranks second in the world in terms of cesarean surgeries, often without a real medical indication. This creates what the Humanization of Childbirth Movement refers to as a "cesarean culture." In this sense, we observe that the childbirth experiences from their families and friends significantly influence each woman's decision-making regarding the mode of delivery. It was also noted that each family's childbirth culture is passed down from generation to generation, less through the transmission of knowledge and more through relationships in various environments that engage their abilities of attention and response. Therefore, we understand that learning about childbirth requires more than just quality information, since it needs to be situated and contextualized. Learning is a complex system that should consider the environments in which humans are the focus of attention and agency, since they respond to environmental stimuli with their life history, their concepts about the world, their family, and their particularities.